Pharmacological lipid lowering for prevention of cardiovascular disease in older adults. (January 2014) - Wiklund, Olov; Pirazzi, Carlo; Romeo, Stefano
SUMMARY An increasing number of patients with cardiovascular disease (CVD) are older adults. New treatments have improved survival but also increased demand for prevention. Comorbidities in older adults contribute to low cholesterol, but accumulating data show that dyslipidemia is a risk factor for CVD in older adults. Although numerous studies show that statin treatment reduces CVD mortality and morbidity, few studies have targeted older adults specifically. However, post-hoc analyses of subgroups indicate that older adults may benefit from statin treatment. Risk reduction in secondary prevention is similar across all age groups, and the limited data available in primary prevention suggest that statins may be considered in high-risk older adult patients. However, statin therapy in older adults should be individualized, taking into account factors more common in this group.